Long-term Results of Arthroscopic Rotator Cuff Repair: Initial Tear Size Matters: A Prospective Study on Clinical and Radiological Results at a Minimum Follow-up of 10 Years. Issue 11 (September 2019) - Randelli, Pietro Simone; Menon, Alessandra; Nocerino, Elisabetta; Aliprandi, Alberto; Feroldi, Francesca Maria; Mazzoleni, Manuel Giovanni; Boveri, Sara; Ambrogi, Federico; Cucchi, Davide
Background: Arthroscopic techniques are now considered the gold standard for treatment of most rotator cuff (RC) tears; however, no consensus exists on the maintenance of results over time, and long-term follow-up data have been reported for few cohorts of patients. Purpose: To present the long-term results associated with the arthroscopic treatment of RC tears and to evaluate associations between preoperative factors and RC integrity at final follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 169 patients were contacted at least 10 years after arthroscopic RC surgery and were invited to a clinical evaluation. Information on preoperative conditions, tear size, subjective satisfaction, and functional scores was collected; isometric strength and range of motion were also measured; and each patient underwent an ultrasound examination to evaluate supraspinatus integrity and a shoulder radiograph to evaluate osteoarthritis. Results: A total of 149 patients (88.2% of the eligible patients) were available for a complete telephonic interview, and 102 patients were available for the final evaluation. Ultrasound revealed an intact supraspinatus in 54 patients (53.47%). By adding the 10 patients who underwent revision surgery to the nonintact group, this percentage would drop to 48.65%. Tear size was associated with supraspinatus integrity in univariate analysis (hazard ratio, 3.04; 95% CI, 1.63-5.69; P = .001) and multivariable analysis (hazard ratio, 2.18; 95% CI, 1.03-4.62; P = .04). However, no significant differences were encountered in the subjective and functional scores collected, with the exception of the Constant-Murley Score, which was significantly higher in patients with smaller tears at the index procedure. Strength testing also revealed significantly superior abduction and flexion strength in this group, and radiographs showed a significantly higher acromion-humeral distance and lower grades of osteoarthritis. Patients with an intact supraspinatus at final follow-up showed superior results in all functional scores, greater satisfaction, superior abduction and flexion strength, higher acromion-humeral distance, and lower grades of osteoarthritis. Conclusion: RC tear size at the time of surgery significantly affects supraspinatus integrity at a minimum follow-up of 10 years. However, a larger tear is not associated with an inferior subjective result, although it negatively influences abduction and flexion strength, range of motion, and osteoarthritis progression. Intraoperative efforts to obtain a durable RC repair are encouraged, since supraspinatus integrity at final follow-up influences clinical and functional outcomes, patient satisfaction, and osteoarthritis progression.